Rising Powers and Grassroots Image Management: Confucius Institutes and China in the Media. (13th November 2019) - Brazys, Samuel; Dukalskis, Alexander
Abstract: This article proposes and tests a mechanism of grassroots image management to explain how rising powers craft an international environment more conducive to their interests. The aim is to promote the state's foreign policy goals by influencing the perceptions of ordinary foreign citizens. To test this mechanism, we examine the impact of China's Confucius Institutes (CIs) as an observable instrument of China's grassroots image management strategy. Using data from the Global Database of Events, Language, and Tone (GDELT), we employ a spatial–temporal approach which finds that proximity to an active CI significantly and substantively improves the tone of media reporting about events relevant to China in that locality. The finding is robust to different specifications and estimation strategies, and is qualitatively consistent with results generated using household opinion data from Afrobarometer surveys. Theoretically, our results suggest the importance of systematically examining presentations and perceptions about rising powers at the popular level, in addition to focusing on elite attitudes, to understand discursive change. More directly, our findings reveal that CIs are helping to improve how China is viewed among foreign publics.